The development of decision support system for the selection of wastewater treatment process and plant design - Md. Sairan, Fadzlin (2009)
Planning and designing wastewater treatment plants (WWTPs) require tedious procedures involving financial, technical and policy matters. The present trend shows the possibility to expedite the process using decision support systems (DSS), which are computer-based tools to solve various engineering and management issues. Thus, this study was conducted to develop a user-friendly DSS, called Wastewater Treatment Plant Design Advisor (WASDA) using Visual Basic 6.0 (VB6) programming language that can support and aid users in planning, designing and managing WWTP system. It could also assist the authority to assess WWTP designs proposed by design engineers and consultants for approval purposes. In addition, the study also emphasized the procedures to apply WASDA in conceptual and process design recommendations for preliminary, primary, secondary and advanced wastewater treatments. WASDA covers municipal and industrial treatment systems, which consists of multiple modules such as equalization tank, neutralization tank, conventional activated sludge, extended aeration, sequencing batch reactor, oxidation ditch, rotating biological contactor, activated carbon adsorption, anaerobic digestion, dissolved air flotation, waste stabilization pond, membrane bioreactor and constructed wetlands. Expert knowledge in the information base was assembled from design textbooks, best practice manuals and guidelines from the Department of Environment (DOE) and Department of Sewerage Services. WASDA was continuously verified and validated during its development through software testing activities i.e. trial-and-error approach, defect and statistical testing; and user acceptance test. The testing activities showed that WASDA is accurate, fast and reliable software, and significant in assisting users to design wastewater treatment plant. In conclusion, WASDA that was blended with Graphical User Interfaces (GUIs) can be a simple and realistic DSS tool to assist engineers and decision-makers to work effectively and efficiently as it will minimize user’s time in making more informed and fast decision. As a knowledge provider, WASDA can assist users to identify problems, observe various alternatives and finally make decision from a range of choices and its financial implications in the shortest time possible.